BIOLOGICAL CONTROL OF SOIL -BORNE FUNGAL PATHOGENS - Magdy Madkour; M. Afifi; E. Metry; I. Ismail (Arab Universities Journal of Agricultural Sciences, 2019)
Seventeen bacterial isolates have been successfully isolated and purified from soil rhizosphere samples collected from different agricultural areas Buhayra, Sharqia and Alqilyubia of Egypt, and screened for production of chitinase enzymes had the highest chitinolytic activities amongst those investigated. Isolate S3-C and S1-C were Identified by biochemical, physiological tests and 16s rRNA gene primer as Bacillus cereus S3C, Gene Bank NCBI accession MK185696 and Bacillus cereus S1C accession MK185697. The production of chitinase by B.cereus S3C and Bacillus cereus S1C was optimized using colloidal chitin medium amended with 1% colloidal chitin at 30°C after five days of incubation. B.cereus S3C had potential for cell wall lysis of many phytopathogenic fungi tested such as Fusarium oxysporum and Rhizoctonia solani Potato phytopathogenic fungi by in vitro antagonistic test. The addition of B. cereus S3C chitinase was more effective than that of B.cereus S1C in increasing the resistance of Potato plants infected with various Soil- borne phytopathogenic fungi.